Between data capitalism and data citizenship - Segura, Maria Soledad (2019)
We discuss two points raised by the articles in this issue which are related to our previous work on media movements in Latin America (Segura & Waisbord 2016). First, we analyze the dimensions of data activism in the region. Recent experiences in Latin America suggest two types of data activism differentiated by goals and spheres of action: social data activism and of data rigths activism. They also have diverse tactics and achievements. Second, we discuss the Global South as the site of counter-epistemic and alternative practices and we wonder about whether the concept of ?data colonialism? adequately captures the dynamics of the digital society in areas of well-entrenched digital divides. We argue that datafication and the opposition to datafication in the South does not develop exactly as in the North given huge political, economic, social and technological differences in the context of the expansion of digital capitalism.